Pharmacokinetics and Pharmacodynamics of Fungal Defensin NZX Against Staphylococcus aureus-Induced Mouse Peritonitis Model - Zheng, Xueling; Yang, Na; Mao, Ruoyu; Hao, Ya; Teng, Da; Wang, Jianhua (Frontiers in Microbiology, 2022)
Staphylococcus aureus (S. aureus) is one of the most common pathogenic bacteria responsible for causing a life-threatening peritonitis disease. NZX, as a variant of fungal defensin plectasin, displayed potent antibacterial activity against S. aureus. In this study, the antibacterial and resistance characteristics, pharmacokinetics, and pharmacodynamics of NZX against S. aureus E 48 and S. aureus E 48-induced mouse peritonitis model were studied, respectively. NZX exhibited a stronger rapid killing activity to S. aureus (minimal inhibitory concentration, 1 μg/mL) compared with linezolid, ampicillin and daptomycin, and serial passaging of S. aureus E 48 for 30 days at 1/2×MIC, NZX had a lower risk of resistance compared with ampicillin and daptomycin. Also, it displayed a high biocompatibility and tolerance to physiological salt, serum environment and phagolysosome proteinase environment, except for acid environment in phagolysosome. The murine serum protein binding rate of NZX was 89.25% measured by ultrafiltration. Based on the free NZX concentration in serum after tail vein administration, the main pharmacokinetic parameters for T1/2, Cmax, Vd, MRT, and AUC ranged from 0.32 to 0.45 h, 2.85 to 20.55 μg/mL, 1469.10 to 2073.90 mL/kg, 0.32 to 0.56 h, and 1.11 to 8.89 μg*h/mL, respectively. Additionally, the in vivo pharmacodynamics against S. aureus demonstrated that NZX administrated twice by tail vein at 20 mg/kg could rescue all infected mice in the lethal mouse peritonitis model. And NZX treatment (20 mg/kg) significantly reduced CFU counts in the liver, lung, and spleen, especially for intracellular bacteria in the peritoneal fluid, which were similar or superior to those of daptomycin. In vivo efficacies of NZX against total bacteria and intracellular bacteria were significantly correlated with three PK/PD indices of ⨍AUC/MIC, ⨍Cmax/MIC, and ⨍T%>MIC analyzed by a sigmoid maximum-effect model. These results showed that NZX may be a potential candidate for treating peritonitis disease caused by intracellular S. aureus.